Efektivitas Pengawasan Produk Keuangan Syariah oleh Otoritas Jasa Keuangan - Adhnin, Ghariza Ardhia; B, Baidhowi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Islamic finance in Indonesia is growing rapidly and contributing to financial inclusion and economic stability. The Financial Services Authority (OJK) plays a role in supervising Islamic financial products to ensure they comply with Islamic regulations and principles. However, supervision still faces challenges, such as the lack of specific regulations, minimal coordination with DSN-MUI, and low Islamic financial literacy. Improvement of regulations, strengthening coordination between institutions, and product innovation are needed so that the Islamic financial industry is more competitive and has an effective supervision system.